2009
DOI: 10.1016/j.micpath.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines expression during Leptospira interrogans serovar Copenhageni infection in resistant BALB/c and susceptible C3H/HeJ mice

Abstract: The role of innate immune responses in protection against leptospirosis remains unclear. We examined the expression of the chemokines CCL2/JE (MCP-1), CCL3/MIP-1 alpha (MIP-1 alpha) and CXCL1/KC (IL-8) regarding resistance and susceptibility to leptospirosis in experimental mice models BALB/c and C3H/HeJ, respectively. A virulent strain of Leptospira interrogans serovar Copenhageni was used in this study. Twenty-five animals of each mouse strain of C3H/HeJ and BALB/c, were infected intraperitoneally with 10(6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
21
1
4
Order By: Relevance
“…IL-17 is known to be responsible for induction of downstream chemokines, such as KC/CXCL1, which are chemotactic for neutrophils (58). The induction of KC/ CXCL1 following infection has been documented for a wide variety of pathogens, including bacterial infections such as Pseudomonas aeruginosa (45,51,56), Chlamydia muridarum (63), Citrobacter rodentium (50,55), Listeria monocytogenes (53), Streptococcus pneumoniae (48,54), Leptospira interrogans (8), and Borrelia burgdorferi (3). In the present studies, KC/ CXCL1 induction was evaluated following systemic A. baumannii infection in C3HeB/FeJ mice.…”
Section: Characterization Of Systemic a Baumannii Infection Five CLmentioning
confidence: 99%
“…IL-17 is known to be responsible for induction of downstream chemokines, such as KC/CXCL1, which are chemotactic for neutrophils (58). The induction of KC/ CXCL1 following infection has been documented for a wide variety of pathogens, including bacterial infections such as Pseudomonas aeruginosa (45,51,56), Chlamydia muridarum (63), Citrobacter rodentium (50,55), Listeria monocytogenes (53), Streptococcus pneumoniae (48,54), Leptospira interrogans (8), and Borrelia burgdorferi (3). In the present studies, KC/ CXCL1 induction was evaluated following systemic A. baumannii infection in C3HeB/FeJ mice.…”
Section: Characterization Of Systemic a Baumannii Infection Five CLmentioning
confidence: 99%
“…Early findings that some strains are refractory to infection by pathogenic Leptospira spirochetes after about 4 weeks of age led to a relative reluctance to conduct investigations with this model. Although this is true for the development of acute disease in BALB/c mice (18)(19)(20), it is also apparent that other strains, such as DBA, C3H, and C57BL/6, can be infected at between 3 and 6 weeks of age and that mice of these strains show signs and symptoms of both acute and chronic infection (8)(9)(10)(11)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…), suggesting that the gene expression levels of these effectors might be predictors of a poor outcome in leptospirosis. Moreover, different expression profiles of the chemokines monocyte chemoattractant protein-1 (MCP-1)/ CCL2, MIP-1␣/CCL3, and IL-8/CXCL8 were noticed in tissue and serum samples between resistant BALB/c and susceptible C3H/HeJ mice inoculated with a high dose of pathogenic L. interrogans serovar Copenhageni (10). These results indicated that resistance to leptospirosis is partially correlated with the increase in MIP-1␣/CCL3 levels observed in BALB/c mice, while an increasing and sustained expression of MCP-1/CCL2 and IL-8/CXCL8 in the lungs of C3H/HeJ mice correlated with the severity and progression of the disease.…”
mentioning
confidence: 99%